Influence of crystal/particle size and gold content of a structured Au/C based sorbent on mercury capture. (November 2017) - Gómez-Giménez, C.; Ballestero, D.; Ferrer, N.; Rubio, B.; Izquierdo, M.T.
Abstract: A sorbent based on gold nanoparticles deposited by direct reduction of a gold salt on a structured carbon surface has been prepared to be used in the mercury capture at low concentrations. A total of 13 samples have been obtained varying preparation conditions (stirring rate, gold salt concentration and contact time). A kinetic study of the gold reduction on the carbon surface has been carried out, indicating that the calculated reaction rate constant corresponds to the diffusion rate equation. The study of the influence of gold salt concentration on the reduction potential of the gold showed that the use of a high concentration gold salt solution shifts the reduction reaction to gold reduction. Mercury capture capacity cannot be directly related with either gold content or average particle size or average crystal size, but the study of the grain size distribution can explain the mercury capture performance of the samples. Graphical abstract: Highlights: Kinetic of Au reduction over carbon structured monoliths is governed by ion diffusion. There is not a relationship between Au crystal size and particle size. Hg capture by Au/C sorbents is not directly related with either Au content or crystal-particle size. GSD from XRD pattern explains the Hg capture by Au/C sorbent.